Hubungan Kecerdasan Emosi dan Problem Solving pada Mahasiswa yang Mengikuti Organisasi BEM Fakultas Psikologi Universitas Gunadarma - Husna Nabilah (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This study aims to examine whether there is a relationship between emotional intelligence and problem solving in students who participate in the BEM organization at the Faculty of Psychology, Gunadarma University. The method used in this research is quantitative research method with TEIQUE-SF scale and PSI scale. The technique used in sampling is purposive sampling. The sample of this study were students who participated in BEM Faculty of Psychology, Gunadarma University. The data analysis technique was carried out using Pearson product moment correlation technique with the help of SPSS application. The results of this study indicate a highly significant positive relationship between emotional intelligence and problem solving with a significance value of 0.000 (p < 0.01) and a pearson correlation value of 0.758